A simulation-based study of scheduling policies to improve the factory performance - Li, Meng (2014)
This project aims to study the effects of open-loop and closed loop job release policies and dispatching rules in an electrical appliance company in Singapore. While maintaining the throughput at the required level with high utilization rate, the project aims to reduce the work-in-process inventory level, as well as to reduce average cycle time, cycle time standard deviation and thus system variability. The developed models and solution methods are validated using actual production data and the results are compared among each other and against the current performance.